Promoting Blended Learning as an Alternative Way to Teach English: from - Zulfa, Puspa Fortuna; Hastuti, Yuniasih Tri (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Recently ICT has important role in learning since modern classroom is changing. It is to ease the learning process for the students studying, in town either in the urban area. One of those learning processes is learning English. The role of ICT is implemented in some innovated learning models, and one of those is blended learning. Blended learning is the combination between the traditional teaching model and the online teaching model. This study is aimed at promoting the blended learning as one of innovated and recommended teaching ways with the advantages and how to implement this learning model for being used to teach English in some probable areas. This study is theoretical based research with accurate sources. In conclusion, this learning model, blended learning, can be considered as one of innovated teaching ways to teach English since it offers new experience for the students, improving the students activeness, improving exam performance, tightening the engagement and interaction, and others.